Mengatur Kecepatan Motor DC dengan menggunakan Metode Fuzzy pada Alat Perontok Padi - Anton Hidayat -; Nasrullah - -; Ramiati - - (Jurnal Ilmiah Poli Rekayasa, 2016)
In designing this device, the rice thresher will be lighter, so it will be easier in lifting, simpler in using so farmers as main users will easier in operating this instrument with featuring speed controllable by applying fuzzy method, and also no fossil fuels used because it utilize sunshine as green energy to drive DC motor. Solar cells are used to absorb sunshine in rice thresher machine because it easier in maintenance. The test results of the rice thresher machine is the reduction of the avarage motor speed by 195 rpm every each five rice straws, in the other hand the maximum electric current is needed to spin the rice threser  is 6 ampere and minimum electric current is 2.2 ampere. Furthermore, to stabilize motor speed at 2000 rpm, the avarage time required is 6 seconds when this machine loaded with rice straws. The eficiency of the rice thresher machine is 96%, it mean the avarage time to thresh the rice is 9 rice straws every each seconds.